Effect Of Leadership Skills And Styles With The Moderating Role Of Personal Initiative In Shaping Malaysian Innovative Women Leaders - Chellappan, Yogeswary (2023)
This study critically analyses past literature on the skills and styles of innovative women leaders. Studies in this direction suggest that the boardroom presence of women leads to more innovative performance.